Cholesky decomposition and well-posedness of Cauchy problem for Fokker-Planck equations with unbounded coefficients - Lee, Haesung (AIMS mathematics, 2025)
This paper explores the well-posedness of the Cauchy problem for the Fokker-Planck equation associated with the partial differential operator $ L $ with low regularity condition. To address uniqueness, we apply a recently developed superposition principle for unbounded coefficients, which reduces the uniqueness problem for the Fokker-Planck equation to the uniqueness of solutions to the martingale problem. Using the Cholesky decomposition algorithm, a standard tool in numerical linear algebra, we construct a lower triangular matrix of functions $ σ $ with suitable regularity such that $ A = σ σ^T $. This formulation allows us to connect the uniqueness of solutions to the martingale problem with the uniqueness of weak solutions to Itô-SDEs. For existence, we rely on established results concerning sub-Markovian semigroups, which enable us to confirm the existence of solutions to the Fokker-Planck equation under general growth conditions expressed as inequalities. Additionally, by imposing further growth conditions on the coefficients, also expressed as inequalities, we establish the ergodicity of the solutions. This work demonstrates the interplay between stochastic analysis and numerical linear algebra in addressing problems related to partial differential equations.